PROGRESSIVE STANCE IN SOCIAL REFORM: A CRITICAL STUDY OF INDIRA BAI - Chandan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research article critically examines Indira Bai, a progressive novel that reflects the social and cultural dynamics of colonial India. Centered on the life of a Brahmin girl born into a conservative yet affluent family, the narrative highlights themes of gender inequality, caste prejudices, widow remarriage, and individual agency against oppressive societal norms. The article explores the transformation of Indira Bai, a widow, into an empowered individual through education and social support. By investigating the novel’s progressive stance, the paper aims to shed light on the broader socio-political implications of reformist literature in 19th-century India.